2021
DOI: 10.26466/opus.905191
|View full text |Cite
|
Sign up to set email alerts
|

Görsel İletişim Tasarım Bölümü Öğrencilerinin Sektörel Logolardaki Renk Tercihleri

Abstract: Firmaların kurumsal kimlik ve logo tasarımında kullanılan renkler, hedef kitle ve müşteri algısının şekillenmesinde büyük bir etkiye sahiptir. Seçilen renkler, marka imajı ve firma hakkında ilk izlenimin oluşmasındaki etkisi bakımından oldukça önemlidir. İşletmeler kurumsal kimliklerini etkili hale getirmek ve hedef kitleye doğrudan ulaşmak üzere; kişilerin ilgisini çekecek, isteklerine hitap edecek renklere logo tasarımında yer vermelidir. İşletmelerin başarısının logo ve ambalaj seçimlerinde kullanılan renkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For a business to make its corporate image effective and reach the target audience directly, the logo design should include colors that can attract people's attention and satisfy their requirements. Zomay studied the favorite colors of many students studying visual design by the use of visual communication design technology, and then using various studies showed that the success of the company is related to the colors used in the logo and packaging choices [2]. In people's daily recreational activities, graffiti culture is becoming more popular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a business to make its corporate image effective and reach the target audience directly, the logo design should include colors that can attract people's attention and satisfy their requirements. Zomay studied the favorite colors of many students studying visual design by the use of visual communication design technology, and then using various studies showed that the success of the company is related to the colors used in the logo and packaging choices [2]. In people's daily recreational activities, graffiti culture is becoming more popular.…”
Section: Introductionmentioning
confidence: 99%
“…According to the comparison between the background model and the current video image, it is found that different pixels are classified as foreground targets, and pixels without distinction are classified as background. It is a common background subtraction [2].…”
Section: Introduction To Background Subtraction Algorithmmentioning
confidence: 99%